Mosaic variants in the LIM homeobox 1 (LHX1) gene contribute to Mayer–Rokitansky–Küster–Hauser (MRKH) syndrome - Dina Kira; Soumia Brakta; Hyung Goo Kim; Jennifer Butler; Lynn P. Chorich; John A. Phillips; Lawrence C. Layman (Human Genetics, 2026)

Safe vitrification of ovarian tissue samples in sealed cryobags - Binnur Eroglu; Lawrence C. Layman; James D. Benson; Adam Z. Higgins; Ali Eroglu (Cryobiology, 2025)

Rare structural variants, aneuploidies, and mosaicism in individuals with Mullerian aplasia detected by optical genome mapping - Soumia Brakta; Zoe A. Hawkins; Nikhil Sahajpal; Natalie Seman; Dina Kira; Lynn P. Chorich; Hyung-Goo Kim; Hongyan Xu; John A. Phillips; Ravindra Kolhe; Lawrence C. Layman (Human Genetics, 2023)

Assessing neophobia and exploration while accounting for social context: an example application in scimitar-horned oryx - Katherine Mertes; Catherine A. Ressijac; Rosana N. Moraes; Lacey F. Hughey; Luisa H. Porto Alegre; Megan Horning; Tara Buk; Arielle Harwood; Lawrence Layman; Christopher Mathews; Morgan Vance; Dolores Reed; et al. (Mammalian Biology, 2022)
Spatial neophobia and exploration are often assessed in nonhuman animals by measuring behavioral responses to novel environments. These traits may especially affect the performance of individuals translocated to novel environments for conservation purposes. Here, we present methods to administer and analyze a minimally invasive novel environment test that accounts for the social context of focal individuals. We used an aerial platform to capture video footage of a captive herd of scimitar-horned oryx ( Oryx dammah ) entering an unfamiliar enclosure. We analyzed footage for seven individually identifiable oryx, scoring their behavioral responses (i.e., latency to enter the enclosure, and movement and posture after entering the enclosure) and social context (i.e., relative position and number of nearby animals). We performed a principal components analysis (PCA) to explore individual traits and responses, and used generalized linear mixed models (GLMMs) to determine the effect of individual traits and social context on individual posture and movement behaviors. Both PCA and GLMMs supported our expectation that social context affects individual behavior: high neighbor density and relative position were negatively related to individual movement, and variation in social context was positively related with head-up postures and movement. Oryx were well differentiated along two principal components that reflected (1) vigilance or caution, and (2) changing social context and age. These methods provide a framework for assessing individual responses to a novel environment in a group setting, which can inform reintroduction and wildlife management efforts, while minimizing interference with animal behavior and management operations.

Genetics of agenesis/hypoplasia of the uterus and vagina: narrowing down the number of candidate genes for Mayer–Rokitansky–Küster–Hauser Syndrome - Sasha Mikhael; Sonal Dugar; Madison Morton; Lynn P. Chorich; Kerlene Berwick Tam; Amy C. Lossie; Hyung-Goo Kim; James Knight; Hugh S. Taylor; Souhrid Mukherjee; John A. Capra; John A. Phillips; et al. (Human Genetics, 2021)

An atypical 12q24.31 microdeletion implicates six genes including a histone demethylase KDM2B and a histone methyltransferase SETD1B in syndromic intellectual disability - Jonathan D. J. Labonne; Kang-Han Lee; Shigeki Iwase; Il-Keun Kong; Michael P. Diamond; Lawrence C. Layman; Cheol-Hee Kim; Hyung-Goo Kim (Human Genetics, 2016)

Novel MED12 gene somatic mutations in women from the Southern United States with symptomatic uterine fibroids - Sunil K. Halder; Archana Laknaur; Jessica Miller; Lawrence C. Layman; Michael Diamond; Ayman Al-Hendy (Molecular Genetics and Genomics, 2015)

Comparison of water isotope-ratio determinations using two cavity ring-down instruments and classical mass spectrometry in continuous ice-core analysis - Olivia J. Maselli; Diedrich Fritzsche; Lawrence Layman; Joseph R. McConnell; Hanno Meyer (Isotopes in Environmental and Health Studies, 2013)